2019
DOI: 10.1177/1078155219832644
|View full text |Cite
|
Sign up to set email alerts
|

Patient engagement in first cycle comprehensive chemotherapy consultation pharmacist services and impact on patient activation

Abstract: Background: Healthcare systems and policy makers worldwide are demonstrating interest in shared decision making, which requires patient activation. Patient activation can be measured using a validated tool called the patient activation measure-10. First cycle comprehensive chemotherapy consultation services (3CS) is provided by an oncology pharmacy team member during a patient encounter at the beginning of the patient's treatment for cancer. Methods: This was a single center, prospective, non-randomized, obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Examples of sources screened out for "Perfunctory Use" defined patient-centered care as any pharmacist service delivered within a Patient-Centered Medical Home, 17 any course in Clinical, Social or Experiential Pharmacy, 18 or used the terminology imprecisely. 19 Examples of sources deemed ineligible for "Insubstantial Use" were publications that appropriately used terms and concepts like shared decision-making, 20 patient-focused care, 21 patient engagement, 22 and patient self-management 23 but lacked operational depth or theoretical exploration applied to patient-centeredness. From the 21 sources selected for categorization and qualitative synthesis, seven classified as "Pharmacy Only," four as "Seminal Only," and 10 as "Pharmacy & Seminal."…”
Section: Resultsmentioning
confidence: 99%
“…Examples of sources screened out for "Perfunctory Use" defined patient-centered care as any pharmacist service delivered within a Patient-Centered Medical Home, 17 any course in Clinical, Social or Experiential Pharmacy, 18 or used the terminology imprecisely. 19 Examples of sources deemed ineligible for "Insubstantial Use" were publications that appropriately used terms and concepts like shared decision-making, 20 patient-focused care, 21 patient engagement, 22 and patient self-management 23 but lacked operational depth or theoretical exploration applied to patient-centeredness. From the 21 sources selected for categorization and qualitative synthesis, seven classified as "Pharmacy Only," four as "Seminal Only," and 10 as "Pharmacy & Seminal."…”
Section: Resultsmentioning
confidence: 99%
“…Raising the importance of assessing the QoL of patients with cancer during the first stage of chemotherapeutic management provides impetus to develop evidence-based and individualized supportive care along the course of cancer treatment. Bates et al (2019), for example, indicated the need to provide FC chemotherapy counseling services to patients with cancer to promote patient engagement and shared decision making on their plan of care. This study serves as a basis in developing a comprehensive and holistic care management plan that supports and alleviates the unfavorable effects of chemotherapeutic treatment and implements interventions that aid in the improvement of overall QoL.…”
Section: Introductionmentioning
confidence: 99%
“…Obviously, the roles of oncology pharmacists in oncology practice are well established in monitoring anticancer drugs, 1 increasing patient engagement in chemotherapy, 2 optimizing therapy effectiveness and preventing adverse effects, 3 improving the safety of chemotherapy, 4,5 medication beliefs and adherence 6 as well as pharmacovigilance. 7 Furthermore, a limited number of reports have described the vital role of clinical pharmacists in interprofessional precision medicine initiatives in oncology practice in the United States.…”
Section: Introductionmentioning
confidence: 99%